Online visual search behaviour of elite and sub-elite bowlers across varying anxiety and challenge levels - Goh, Wan Xiu (2014)
Current visual search literature has predominantly investigated gaze behaviour in a pre-movement programming role. However, different visual search behavior (VS) may be present in sports that involve a long movement execution such as the 5-step approach in bowling. Thus, the VS of 12 elite and 12 sub-elite bowlers during movement execution (online-VS) were analysed across four conditions of varying anxiety and challenge levels. Ten shots were bowled in each condition, whereby the percentage duration of online phase (%online), mean number of fixations (NR) and percentage duration of fixation (%D) to each area of interest (AOI) were measured. Expertise differences lie in NR and %D whereby the elite bowlers had fewer fixations of longer durations (p < .05). While executing the bowl, all bowlers tend to fixate on the right and middle dots and arrows; locations that are closer to the foul line. Aiming at nearer targets, compared to locations further down the lane may increase the chances of releasing the ball at the optimal location for the best trajectory. With anxiety, bowlers rushed their approach (p < .05), but increased their %D to the right dots and peripheral left arrows (p < .01). The results reflect an increased effort to focus their aim, but with the propensity to be more distracted. Overall, online-VS do differentiate between levels of expertise and anxiety, though no significant interaction was observed. Analysing the sequence of fixation and movement together may provide greater resolution into the online-VS phenomenon.